Analysis of the capillary-force-based μDMFC (micro direct methanol fuel cell) supplied with pure methanol. (September 2015) - Yuan, Zhenyu; Yang, Jie; Ye, Ning; Li, Zipeng; Sun, Yuge; Shen, Hongyuan
Abstract: In this paper, a capillary-force-based μDMFC(micro direct methanol fuel cell) supplied with pure methanol is presented. A 2D (two-dimensional) steady state model is established to investigate the methanol distribution inside the low concentration chamber with the barrier layer patterned on different diffusion materials. Simulation results illustrate that both methanol diffusion coefficient of the barrier layer and the effective mass transfer area have significant effects on inner methanol distribution. In addition, the effect of capillary force at both inlet and outlet ends of the capillary channel between the pure methanol and the low concentration methanol are simulated. To further prove the feasibility of this supply method, a 3D (three-dimensional) transient model is finally established to monitor the variation of methanol concentration with the change of the operating duration. Highlights: A capillary-force-based μDMFC supplied with pure methanol is presented. The methanol distribution at different diffusion coefficients is modeled. The capillary forces in both inlet and outlet channels of methanol are simulated. The methanol variation with the change of the operating duration is calculated.